Asymmetric Effects Of Oil Prices And Exchange Rates On Sectoral Stock Indices In South Asian Countries - Asim, Muhammad (2024)
Globalization has grown but at accelerating uncertainties. Therefore, contagion and spillover effects among financial markets have become the center of research in finance in the past decades. Most of the past studies on stock market mainly consisted of two streams first one is the impact studies on stocks and another one is spillover studies. Existing impact studies mainly examine the relationship between stocks and key factors such as oil price and exchange rate but do not account for asymmetric effects and sectoral effects. These studies utilize aggregate index which normally suffers from aggregation bias. Secondly, apart from that, numerous studies that assess the financial shock transmissions mainly focus on developed nations but less attention was given to the emerging south asian region. So far, to the best knowledge of the author, none of the previous studies measure directional spillover at the sectoral level for south asian countries. Taking note of the issues mentioned, the present study is designed into two parts. First part of this study evaluates asymmetric impacts of both up-down movements in oil prices and exchange rates on sectorial stock prices of india, pakistan, and sri lanka (ips). For this purpose, this study adopts the nonlinear autoregressive distributed lag (nardl) given by shin et al. (2014). Second, this study examines the connectedness among the oil, forex, and sectoral stock returns of ips. The spillover index framework given by diebold and yilmaz (2012) and barunik and krehlik (2018) are used for respective time-domain and frequency-domain spillover analysis.